2016
DOI: 10.3390/ijms17040454
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dimethylarginine versus Proton Pump Inhibitors Usage in Patients with Stable Coronary Artery Disease: A Cross-Sectional Study

Abstract: A recent experimental study suggested that proton pump inhibitors (PPI), widely used to prevent gastroduodenal complications of dual antiplatelet therapy, may increase the accumulation of the endogenous nitric oxide synthesis antagonist asymmetric dimethylarginine (ADMA), an adverse outcome predictor. Our aim was to assess the effect of PPI usage on circulating ADMA in coronary artery disease (CAD). Plasma ADMA levels were compared according to PPI use for ≥1 month prior to admission in 128 previously describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…In particular, L-N G -nitroarginine methyl ester may affect glycaemia also via adrenal epinephrine release 36 , and the inhibition of the insulin-degrading enzyme through S-nitrosylation was demonstrated only in vitro at high concentrations of artificial putative NO donors and consequent exposure to supraphysiological levels of NO liberated from these compounds 35 . Moreover, in a recent clinical observational study 37 , we did not confirm the PPI-ADMA interaction.…”
Section: Discussioncontrasting
confidence: 86%
“…In particular, L-N G -nitroarginine methyl ester may affect glycaemia also via adrenal epinephrine release 36 , and the inhibition of the insulin-degrading enzyme through S-nitrosylation was demonstrated only in vitro at high concentrations of artificial putative NO donors and consequent exposure to supraphysiological levels of NO liberated from these compounds 35 . Moreover, in a recent clinical observational study 37 , we did not confirm the PPI-ADMA interaction.…”
Section: Discussioncontrasting
confidence: 86%
“…Although PPI use was associated with an increase in plasma ADMA, no adverse effect on vascular function was evident . A further study conducted by Kruszelnicka et al suggested that PPI use did not appear to increase plasma ADMA in a study cohort of nondiabetic men with coronary artery disease. Due to this conflicting evidence, the association between PPIs and subsequent dysregulation of NO as a potential explanation for the observed increase in cardiovascular risk remains controversial.…”
Section: Discussionmentioning
confidence: 95%
“…ADMA inhibits the nitric oxide synthase, which may lead to an acceleration of atherosclerosis . However, clinically relevant impacts of PPIs on plasma ADMA levels have been inconsistent . It has also been hypothesized that the elevated gastric pH, caused by either PPI or H2RA, decreases conversion of dietary nitrate and nitrite to nitric oxide (NO), leading to endothelial dysfunction .…”
Section: Discussionmentioning
confidence: 99%